Are We Listening to Elders? Intergenerational Wisdom as a Protective Factor Against Bullying in Diverse Academic Spaces - Mariem (Magyar Gerontológia, 2025)
Bullying remains one of the most persistent challenges in educational and academic environments, exerting a wide-ranging impact on students’ psychological well-being, physical health, and academic achievement.